2016
DOI: 10.1016/j.biochi.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

From infancy to aging: Biological and behavioral modifiers of Fetuin-A

Abstract: Fetuin-A is a multifunctional protein which inhibits ectopic calcification and insulin receptor phosphorylation. It may also promote insulin resistance by activation of toll-like receptor 4 pro-inflammatory cascade. Increased levels of Fetuin-A have been associated with obesity and related comorbidities such as type 2 diabetes and cardiovascular disease, therefore, it has been suggested as a potential therapeutic target for intervention. However, in addition to its role in disease pathophysiology, Fetuin-A is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 101 publications
(170 reference statements)
0
32
0
Order By: Relevance
“…Following collagen, AHSG is one of the most abundant proteins in bone and its ability to bind calcium and other minerals supports the notion that it is essential for osteogenesis [74,75]. Current studies suggest that circulating AHSG is highest during infancy, declines in childhood and varies in adults owing to genetic factors, obesity and diet [73]. AHSG might also be impacted by the natural ageing process [76].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Following collagen, AHSG is one of the most abundant proteins in bone and its ability to bind calcium and other minerals supports the notion that it is essential for osteogenesis [74,75]. Current studies suggest that circulating AHSG is highest during infancy, declines in childhood and varies in adults owing to genetic factors, obesity and diet [73]. AHSG might also be impacted by the natural ageing process [76].…”
Section: Discussionmentioning
confidence: 98%
“…Owing to high concentrations of AHSG in fetal serum, multiple functions related to development have been suggested [72,73]. Following collagen, AHSG is one of the most abundant proteins in bone and its ability to bind calcium and other minerals supports the notion that it is essential for osteogenesis [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…These include, for example, a lack of reference values, inconsistent values from various commercial enzyme-linked immunosorbent assays (ELISA), and the unknown effect of post-translational modifications (PTMs) on hFet clinical measurements. 13 One source of confusion may also originate from some in vitro studies, where recombinant human fetuin was used. 14 , 15 Serum hFet is predominantly synthesized in the liver, where its N-glycosylation pattern originates.…”
Section: Introductionmentioning
confidence: 99%
“…It is known to have various biological functions, including the prevention of tissue calcification and maintenance of calcium-phosphorus balance [1011]. Data obtained in recent experimental studies showed that elevated levels of fetuin-A lead to IR by disturbing insulin receptor signalling [11].…”
Section: Introductionmentioning
confidence: 99%